GROWTH RESPONSE OF COCOA SEEDLINGS (Theobroma cacao L.) AGAINST THE DOSAGE OF COCOA PEEL COMPOST - Irene Tri Okten Nainggolan; Maria Imelda Humoen; Siti Rahmah; Egidius Naitkakin (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
The increasing productivity of cocoa in East Nusa Tenggara generates cocoa pod husk waste that has the potential to be utilized as organic compost. This study aimed to determine the effect of cocoa pod husk compost application on the growth of cocoa seedlings (Theobroma cacao L.) and to identify the most effective dosage. The research was conducted from April to June 2026 at the Green House of the Military Logistics Vocational Faculty, Republic of Indonesia Defense University, Belu Regency, using a Completely Randomized Design (CRD) with five treatments, namely P0 (without compost), P1 (50 g/polybag), P2 (75 g/polybag), P3 (100 g/polybag), and P4 (150 g/polybag), each replicated three times. The results showed that the application of cocoa pod husk compost improved the growth of cocoa seedlings. Treatment P4 (150 g/polybag) produced the best results with a plant height of 20.44 cm, stem diameter of 6.19 mm, number of leaves of 6.67, leaf length of 12.17 cm, leaf width of 6.61 cm, fresh root weight of 6.61 g, and dry root weight of 2.46 g. Cocoa pod husk compost has the potential to be used as an organic fertilizer to improve the growth of cocoa seedlings.